Depression among patients undergoing maintenance hemodialysis at a tertiary care center in Kathmandu, Nepal - Manandhar, Nora Ranjitkar; Shakya, Rabi; Pandey, Bimal; Wagley, Pratik (Journal of Patan Academy of Health Sciences, 2018)
Introductions:Patients with chronic kidney disease have a high burden of somatic symptoms which may be due to depression. This study analyses occurrence of depression in patients with chronic kidney disease (CKD) undergoing hemodialysis (HD) at a tertiary care center in Kathmandu, Nepal. Methods: This is a retrospective study done at Patan Hospital, a tertiary care teaching hospital of Patan Academy of Health sciences, Lalitpur, Nepal. Translated in Nepali language and validated Beck Depression Inventory (BDI) was used. A cut-off of 16/17 was used to define depression. Results: Altogether 56 patients were included, mean age 54.375±17.87 years, time on HD 25.06±21.58 months, BDI score 19.18±10.16. The prevalence of depression was 51.8%. There was no significant differences of BDI score and rate of depression in genders, housing status, education level, alcohol intake, presence of co-morbidity and shift of HD. However, there was a significant association of BDI score and the employment status, p=0.026 and the affordability of erythropoiesis stimulating agent, p=0.033. Conclusions: Depression was common in patients undergoing hemodialysis treatment and the rate of depression was significantly lower in the patients who were employed and used of erythropoiesis stimulating agent.